Design of Oversampled DFT Modulated Filter Banks Optimized for Acoustic Echo Cancellation - Li, Qin; Chen, Wei-ge; He, Chao; Malvar, Henrique; Malvar, Henrique S. (International Conference on Acoustics, Speech and Signal Processing, 2009)
This paper describes a method for designing oversampled DFT filter banks (FB) optimized for subband acoustic echo cancellation (AEC). For this application, the design requirements typically are good echo cancellation quality, low delay, small reconstruction error, and low computation complexity. Our method explicitly includes a model for echo return loss enhancement (ERLE) as part of the optimization criteria. Convergence of the high-dimensional, nonlinear optimization problem is facilitated by decorrelating the prototype filter impulse response via a discreet cosine transform (DCT), discarding many insignificant coefficients and thus reducing the dimensionality of the search. The experimental results demonstrate the effectiveness of our design and the effects on the performance of AEC, with ELRE improvements on the order of 3 dB or better. The method is flexible and could also be extended to other application domains.